Penerapan Sistem Biaya Standar pada Perusahaan Dagang “Supermarket’’ - Valentina Monoarfa; Yuliana Ihsan Baili; Karsum yahya; Anisa Rahmawati; Susmiyati Talibana (Economic Reviews Journal, 2025)
The implementation of a standard cost system in a trading company such as a supermarket is an important strategy in effective and efficient cost management. A standard cost system is a method for determining costs that should occur based on certain factors, such as raw material costs, labor, and overhead. By using this system, companies can plan, control, and evaluate costs that occur in daily operations. The main purpose of implementing a standard cost system is to improve budgeting accuracy, control cost deviations, and optimize resource use. In supermarket companies, a standard cost system can be used to calculate the cost of goods sold (COGS), labor costs, and other operational costs, making it easier to set prices and control costs. In addition, this system also provides clearer information for management in decision making, both related to budget planning, pricing strategies, and performance evaluations. The implementation of a standard cost system is expected to improve the efficiency and competitiveness of supermarkets in facing increasingly competitive market challenges.